Assessment of physiological water use efficiency of citrus germplasm - Albrizio R.; Steduto P. (Improvement of the citrus sector by the setting up of the common conservation strategies for the free exchange of healthy citrus genetic resources, 2001)
An account is given of the assessment of physiological water use efficiency for the complete characterization of citrus biodiversity is given. This approach may allow to link genetic and field issues thus inducing the farmers to take sounder actions. Leaf gas-exchange measurements are applied by portable photosynthesis system, which needs to be used for a couple of days during two different growth stages for each single biotype. All leaves measured will also be analyzed for nitrogen content.